Biologia populacional e reprodutiva do caranguejo Guaiamum (Cardisoma guanhumi Latreille, 1828) do estuário do Rio Jaguaribe (CE) - Nobre, Daniel Esses (2024)
Life history theory studies the trade-offs between growth, reproduction, and maintenance and how different organisms allocate their energies in response to different environmental pressures. The crab Cardisoma guanhumi Latreille, 1828 is a species of great ecological and economic importance, but fishing and the suppression of its habitat have been altering features of its life history. Thus, the objectives of the present work were to review Brazilian legislation on crab conservation and analyze traits of its population and reproductive biology to investigate possible changes in its life history. Legislation for the sustainable use of guaiamum has existed since 2002 and was modified over 20 years, following some changes in the biology of the species, which is today considered Vulnerable (VU) to extinction, with rules for sustainable use and conservation of stocks. However, each population has peculiarities and rules for the entire country tend to make artisanal fishing unfeasible. In the Jaguaribe River estuary (CE), collections took place bimonthly, from March 2023 to January 2024, with 169 individuals captured. The animals were separated by sex, measured and dissected for histological analysis of the gonads. The sex ratio was 1:1, demonstrating population balance. Sex, weight, chela length, abdomen width and rainfall have a significant relationship (p < 0.05) with carapace width. The sizes at first morphological maturation were 5.84 and 6.0 cm, while physiological sizes were 5.16 and 4.49 cm, for females and males, respectively. When comparing with data on maturity sizes obtained in 2008, it is noted that the population is maturing earlier, with a statistical difference for gonadal maturation (p < 0.05). The gonadosomatic index indicated a reproductive period between the months of November and March, with spawning between March and May, months close to and within the region's rainy season. The number of open and closed burrows indicated a period of greater molting activity in the drier months, from May to September. The population density was 2.04 individuals/m², with an estimated abundance of 13,668 individuals at the mouth of the estuary (6,700 m²). The results presented here show that the environment is selecting individuals with less energy allocation in somatic growth and greater investment in reproduction, which, as a result, may be increasing their fecundity with the production of a greater quantity of eggs per clutch, in order to guarantee the existence of future generations